Clinical characteristics and outcomes of pregnancies at-risk of hemolytic disease of the fetus and newborn in Sweden, Finland, and Denmark: a population-based register studyAJOG Global Reports at a Glance - Kelvin H.M. Kwok, PhD; Mika Gissler, PhD; Mette Ø. Thunbo, MD, PhD; Elizabeth C. Hsia, MD, MSCE; May Lee Tjoa, PhD; Shengxin Liu, PhD; Malin Almgren, PhD; Vedran Stefanovic, MD, PhD; Lars H. Pedersen, MD, PhD; Agneta Wikman, MD, PhD (AJOG Global Reports, 2025)
Background: Red blood cell (RBC) alloimmunization is an immune response where the maternal immune system produces antibodies against fetal RBCs, which can lead to hemolytic disease of the fetus and newborn (HDFN). Despite the significant clinical burden of HDFN, there are few large international cohorts that focus on perinatal care and outcomes of at-risk pregnancies. Objective: To describe the maternal characteristics and outcomes of pregnancies affected by RBC alloimmunization, as well as the characteristics and outcomes of neonates from such pregnancies. Study Design: Utilizing data from nationwide health registers, this population-based cohort study identified all singleton pregnancies in individuals who had ≥1 pregnancy monitored or treated for potential alloimmunization, or ≥1 child with a postnatal diagnosis of HDFN-related conditions, between January 1, 2000, and December 31, 2021, in Sweden and Finland, and between January 1, 1997, and December 31, 2018, in Denmark. Among the identified pregnancies, those with a diagnosis of maternal care for alloimmunization or fetal hydrops, or neonates with a postnatal diagnosis of HDFN-related conditions, were categorized as HDFN pregnancies. The remaining pregnancies—sibling pregnancies that may have been at risk of alloimmunization but did not receive any alloimmunization- or HDFN-related diagnosis—were categorized as non-HDFN pregnancies. Results: This study included 14,732 singleton pregnancies in Sweden, 5863 in Finland, and 11,964 in Denmark. Among these pregnancies, 7391 (50%) in Sweden, 2885 (49%) in Finland, and 6150 (51%) in Denmark were categorized as HDFN pregnancies. Maternal complications and stillbirth rates were comparable between HDFN and non-HDFN pregnancies. Caesarean deliveries were more frequent in HDFN pregnancies. A total of 14,519 neonates in Sweden, 5827 in Finland, and 11,803 in Denmark were born to all pregnancies identified. Of these, 7289 (50%), 2849 (49%), and 6076 (51%) had HDFN. Among the neonates with HDFN, 27% in Sweden, 38% in Finland, and 12% in Denmark received HDFN-related treatment, including intrauterine transfusion (IUT; data unavailable for Finland), neonatal transfusion, and phototherapy. Compared to non-HDFN neonates, those in the IUT and neonatal transfusion groups had lower gestational age, birth weight and length, and higher rates of neonatal unit admission, and were more frequently diagnosed postnatally with growth disturbances and disorders of the nervous system. Conclusion: This is a comprehensive overview of perinatal characteristics and outcomes of pregnancies at risk of HDFN in Sweden, Finland, and Denmark. Our findings highlight the significant unmet need in perinatal care among neonates with HDFN, particularly those treated with IUT or neonatal transfusion. Further research is warranted to improve the management of severe HDFN pregnancies.